2021
DOI: 10.1021/acs.jpcc.1c04495
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learned Corrections to Mean-Field Microkinetic Models at the Fast Diffusion Limit

Abstract: We present a machine learning-based formalism to correct the mean-field assumption in microkinetic models to incorporate adsorbate interactions and surface inhomogeneity at the fast diffusion limit. Lattice Monte Carlo simulations are used to compute the macroscopic reaction rate in the presence of adsorbate interaction at different values of surface coverage. This dataset is then used to train an artificial neural network to compute precise reaction rates as a function of surface coverage of intermediates, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…If the time scales of the various processes are many orders of magnitude apart, the catalytic reaction network can be treated as a singularly perturbed system, where the quasi-equilibrium-based scheme outlined above can be used. In fact, such concepts have been used to calculate ensemble-averaged transition probabilities in KMC simulations where there is a large time scale disparity between adsorbate diffusion and reaction. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the time scales of the various processes are many orders of magnitude apart, the catalytic reaction network can be treated as a singularly perturbed system, where the quasi-equilibrium-based scheme outlined above can be used. In fact, such concepts have been used to calculate ensemble-averaged transition probabilities in KMC simulations where there is a large time scale disparity between adsorbate diffusion and reaction. ,, …”
Section: Resultsmentioning
confidence: 99%
“…In fact, such concepts have been used to calculate ensemble-averaged transition probabilities in KMC simulations where there is a large time scale disparity between adsorbate diffusion and reaction. 52,57,58…”
Section: Kinetic Simulations Of H 2 Desorption From Pt 3 (-H)mentioning
confidence: 99%
“…The spectral analysis for our simple fluxional catalyst model also illustrates that transient relaxation of the intermediate abundances may take an extremely long time. Despite the simplicity of the model, these considerations will likely remain important for more complex systems with interacting adsorbates, 90 Langmuir−Hinshelwood steps, 90 and transient association/dissociation of the active centers. 91,92 The spectral analysis approach should be applicable to more complicated mechanisms and large ensembles of intermediates for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…25 A different approach was chosen by Tian and Rangarajan, who combined kinetic Monte Carlo studies with an artificial neural network to modify mean-field microkinetic models for the impact of surface coverage. 26 They showed that using this correction leads to a significantly better agreement between results for kinetic Monte Carlo simulation and microkinetic modeling.…”
Section: Artificial Intelligence For the Automated Discovery Of Heter...mentioning
confidence: 99%
“…Over the past years, methods were developed that use machine learning to predict favorable coverage patterns of CO on Pt surfaces or NO and propyne on mixed metallic surfaces . A different approach was chosen by Tian and Rangarajan, who combined kinetic Monte Carlo studies with an artificial neural network to modify mean-field microkinetic models for the impact of surface coverage . They showed that using this correction leads to a significantly better agreement between results for kinetic Monte Carlo simulation and microkinetic modeling.…”
Section: Grand Challenge I: Machine Learning and Artificial Intellige...mentioning
confidence: 99%